Gambaran Perilaku Pencegahan Penyakit Malaria di Sumatera Selatan (Analisis Lanjut Riskesdas 2018) - Yanelza Supranelfy; Reni Oktarina (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2021)
Malaria is a disease caused by a parasite (protozoa) of the genus plasmodium, transmitted through the Anopheles mosquito's bite Prevention by vector control and preventing mosquito bites to humans needs to be carried out to break the chain of transmission. This study aims to find out at the description of malaria prevention conducted by community in South Sumatera. This is descriptive research with a cross-sectional approach using data from the results of the Basic Health Research (Riskesdas) 2018. The research sample were 33,566 people spread in 17 districts/cities in South Sumatera. The respondents were dominant in the 36-45 years age group, male, had low education, and had a job as a farmer. The results showed that the most widely used prevention of mosquito bites in South Sumatra was using non-insecticide mosquito nets and mosquito repellents. Meanwhile, insecticide-treated mosquito nets that are often used are generally more than three years. The respondents who live in areas that have obtained a malaria elimination certificate and respondents with low levels of education tend to sleep using insecticide-treated mosquito nets.